Actividades de Ocio y Recreación del turista de la provincia de Cotopaxi”. En tiempos de pandemia - Albán García, Nathaly Carolina (2022)
The present research project was made with the purpose of comparing the tourist leisure and recreation activities in the Cotopaxi province, before-after the pandemic, which it was made a longitudinal research with a quantitative approach, comparative relational scope, whose main aim was to compare these activities, through the tourists characterization from Cotopaxi province, thus, contributing to the province tourism development, in order to observe the transformation, was tourism suffered its activities, due to Covid-19, it worked with two aims, which were to survey and analyze, for its fulfillment, it proceeded to information compilation, through the internet, web pages, virtual libraries, PDOT Territorial development and planning plan from Cotopaxi province, pdfs, thesis repositories, reports, magazine articles, the same ones that helped to elaborate the foundation technical scientist, thus, continuing with the surveys application to the infinite study population, which was calculated, by means non-probabilistic sampling formula, resulting 385 study samples, in order to get the four variables, what were: activities, frequency, travel and expense companions, through inferential statistics and the got data interpretation, by means the work instrument. Concluding with the results, it could observe, what there was a great change in the activities and tourists behavior, since, with the arrival of the pandemic, people replaced their daily activities, since they were forced to stay their home alone or with others, his/her family, another change that occurred was the reduction of their economy, due to the fact, what several them lost their income source and therefore, they had to reduce their expenses.